LGG-55. Autophagy sensitizes CNS tumors to targeted therapy by lowering their apoptotic threshold. (3rd June 2022) - Crespo, Michele; Zahedi, Shadi; Morin, Andrew; Wodetzki, Darya; Caino, Cecilia; Levy, Jean Mulcahy
Abstract: Autophagy inhibition improves the effectiveness and overcomes RAF pathway inhibition (RAFi) resistance across multiple CNS tumors and molecularly distinct resistance mechanisms. Mechanistic links between autophagy and apoptotic cell death may explain this ability to improve RAFi response and reverse resistance. RAFi sensitive (MAF 794, AM38) and resistant (MAF 794R, MAF 905-3, AM38R, B76) BRAFV600E CNS tumor cell lines were analyzed at baseline, following RAFi (vemurafenib), autophagy inhibition (chloroquine or shRNAs), and combination therapy. Growth assays and caspase activation were monitored by Incucyte Zoom. qRT-PCR evaluated key pro-apoptotic BH3-only members of the BCL-2 family. Broad BH-3 profiling was completed using the Letai JC-1 Plate-Based protocol. Western blot analysis assessed protein levels. Combination pharmacologic treatment caused alterations in key pro-apoptotic BH3-only proteins including an increase in BNIP3L and PUMA. Genetically inhibiting autophagy with shRNAs for ATG5 and ATG7 (proteins required for formation of the autophagosome) produced similar results with increases in both protein and mRNA levels of BNIP3L and PUMA following RAFi treatment. This suggested autophagy-mediated regulation of BH3 proteins functions to determine cellular apoptotic threshold. Caspase activation demonstrated increased effectiveness of combined RAFi and autophagy inhibition overcoming the apoptotic threshold compared to single drug treatment. BH3 profiling demonstrated a dependence on BCL-2 to inhibit apoptosis. BH3 mimetics competitively bind to pro-survival BCL-2 family members, blocking their protective effects and pushing tumor cells towards apoptosis. Autophagy inhibition can also improve treatment response by overcoming the apoptotic threshold in RAFi resistant cells and magnifying the apoptotic response in sensitive cells. BH3 profiling reveals CNS BRAFV600E are BCL-2 dependent cells, unprimed for apoptosis, which may be good candidates for additional treatment with BH3 mimetics such as venetoclax. This presents an attractive treatment for MAPK activated CNS tumors by enhancing apoptotic cell death by targeting the MAPK pathway, autophagy and BH3.